VD_FINDINFO Arrêt / 2024 / 1068 vom 24. Januar 2025 - VD Tribunal cantonal (2025)
EXPERTISE PLURIDISCIPLINAIRE, ÉVALUATION DE L'INVALIDITÉ, AIASSURANCE, FIBROMYALGIE, ÂGE, CHANGEMENT DE PROFESSION | 28 LAI, 29 LAI, 4 al. 1 LAI, 16 LPGA, 17 al. 1 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA, 88a RAI